Standing in the gap : army outposts, picket stations, and the pacification of the Texas frontier, 1866-1886 - Uglow, Loyd, 1952- (Texas Christian University Press, 2001)
"After the Civil War, the United States Army faced a tremendous challenge on the Texas frontier. Military authorities had to overcome major obstacles in mobility and communications, and they had to learn a far different kind of warfare to defeat the Kiowa, Apache, and Comanche Indians."